The Utilization of Google Sites as a Professional E-Portfolio for Teachers Moving Force X Pringsewu District - Kurniati, Kurniati; Kayyis, Rahmatika; Safitri, Aninda Faradila; Wanda, Aldyto Pramys (English Teaching and Linguistics Journal (ETLiJ), 2025)
This research examines the use of Google Sites as an e-portfolio medium by Class X teachers in Pringsewu Regency, Lampung, through a descriptive qualitative approach. The research focuses on understanding the usage, response, and results of utilizing Google Sites as an e-portfolio media in the context of teachers' professional reflection. Data collection was conducted through interviews, observations, and content analysis of e-portfolios created using Google Sites. The research subjects were Class X teachers who have used Google Sites as an e-portfolio tool. The research results are expected to serve as a foundation for developing the Teacher Mobilization Program implemented by the Teacher Mobilization Center. The research output will be published in National Journal, and documented through social media platforms Facebook and YouTube to reach a wider audience. This research provides significant contributions to understanding the utilization of digital technology for teachers' professional development and improving education quality in Pringsewu Regency.